2018
DOI: 10.1007/s10930-018-9789-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characterization of Pseudomonas aeruginosa Recombinant l.Asparaginase

Abstract: Recombinant .asparaginase, L.ASNase, from Pseudomonas aeruginosa was purified using nickel affinitychromatography. The affinity purified L.ASNase exhibited a protein band with a molecular weight of 72.4 kDa on a native polyacrylamide gel and 36.276 kDa using SDS-PAGE. The activity of the purified L.ASNase was enhanced by Mg and inhibited by Zn at a concentration of 5 mM. The specificity of the recombinant L.ASNase towards different substrates was examined, and it was found that the enzyme showed the highest ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The enzyme-substrate combinations were incubated for 10 min at 37°C before being stopped by adding 100 µl of 1.5 M TCA. The amount of ammonia emitted was estimated using Nessler's reagent [ 21 ] and an ammonium sulfate solution as a standard, after which the samples were centrifuged and used for ammonia estimation. An international unit (UI) of L-asparaginase is defined as the amount of enzyme necessary to release one micromole of ammonia per minute at saturating substrate concentration under the assay conditions [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme-substrate combinations were incubated for 10 min at 37°C before being stopped by adding 100 µl of 1.5 M TCA. The amount of ammonia emitted was estimated using Nessler's reagent [ 21 ] and an ammonium sulfate solution as a standard, after which the samples were centrifuged and used for ammonia estimation. An international unit (UI) of L-asparaginase is defined as the amount of enzyme necessary to release one micromole of ammonia per minute at saturating substrate concentration under the assay conditions [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…L-asparaginase activity was frequently reported in plants, micro-organisms (bacteria, fungi, and actinomycetes), animals, and in the serum of certain rodents but was not isolated from a human source (Lalitha and Ramanjaneyulu, 2016). Many genera of bacteria, Bacillus circuans (Prakasham et al, 2010), Bacilus brevis (Narta et al, 2011), Pseudomonas flurescens (Sinha et al, 2015), Pseudomonas aeruginosa (Saeed et al, 2018), and Escherichia coli (Kante et al, 2019) are reported as Lasparaginase producers.…”
Section: Introductionmentioning
confidence: 99%
“…Nessler's reagent is widely used to quantify ASNase activity, yet little attention has been paid to the effects of salts present in the analyte that can yield erroneous estimates of enzyme activity 22–28 . Here, we determined that the salts of Co 2+ , Fe 2+ , Mg 2+ , Mn 2+ and Ni 2+ interfered with NH 3 quantification using Nessler's reagent, while the salts of Ca 2+ , Cu 2+ , Mo 2+ , Na + and Zn 2+ did not.…”
Section: Resultsmentioning
confidence: 89%